Gestational Diabetes But Not Prepregnancy Overweight Predicts for Cardiometabolic Markers in Offspring Twenty Years Later - Jouko Sundvall; Karoliina Wehkalampi; Nina Kaseva; Dieter Wolke; Hanna-Maria Matinolli; Kati Heinonen; Marjaana Tikanmäki; Marja Vääräsmäki; Eero Kajantie; Aulikki Lano; Sture Andersson; Marika Sipola; et al. (The Journal of Clinical Endocrinology & Metabolism, 2022)
Context Maternal gestational diabetes mellitus (GDM) and prepregnancy overweight/obesity [body mass index (BMI) ≥25 kg/m2] might adversely affect offspring cardiometabolic health. Objective To assess the associations between maternal GDM and prepregnancy overweight/obesity with adult offspring cardiometabolic risk factors. Design Longitudinal cohort study (ESTER Maternal Pregnancy Disorders Study and the Arvo Ylppö Longitudinal Study). Setting Province of Uusimaa and Northern Finland. Participants At a mean age of 24.1 ± 1.3 years, we classified offspring as offspring of mothers with GDM regardless of the prepregnancy BMI (OGDM; n = 193); normoglycemic mothers with prepregnancy overweight/obesity (ONO; n = 157); and normoglycemic mothers with prepregnancy BMI <25 kg/m2 (controls; n = 556). Main Outcome Measures We assessed the cardiometabolic biomarkers from blood and measured the blood pressure at rest and heart rate. Results Compared with the controls, the OGDM and ONO groups had greater fasting glucose (1.6%; 95% CI, 0.1% to 3.1%; and 2.3%; 95% CI, 0.5% to 4.3%, respectively) and insulin (12.7%; 95% CI, 4.4% to 21.9%; and 8.7%; 95% CI, 0.2% to 17.8%). These differences attenuated to nonsignificance when adjusted for confounders and/or current offspring characteristics, including BMI or body fat percentage. The OGDM group had lower SHBG (men, −12.4%; 95% CI, −20.2% to −3.9%; women, −33.2%; 95% CI, −46.3% to −16.8%), high-density lipoprotein (−6.6%; 95% CI, −10.9% to −2.2%), and apolipoprotein A1 (−4.5%; 95% CI, −7.5% to −1.4%). These differences survived the adjustments. The heart rate and other biomarkers were similar among the groups. Conclusions Adult offspring of mothers with GDM have increased markers of insulin resistance and a more atherogenic lipid profile. These were only partly explained by confounders or current offspring adiposity. Maternal prepregnancy overweight/obesity was associated with impaired offspring glucose regulation, which was explained by confounders and/or current adiposity.